Development Of Lake Shuji Tourism Potential On Socio-Economic Community In Lembak Village - Ningrum, Tia; Oktavia, Maharani; Taufik, Mirna; Utomo, Budi; Heldayani, Eni; Nuranisa, Nuranisa; Rosita, Laili; Asiyah, Siti (Universitas Veteran Bangun Nusantara, 2021)
The development of tourism potential is currently one of the factors in increasing people's income. The purpose of this study was to determine the development of the tourism potential of Lake Shuji on the socio-economic community in Lembak Village.Qualitative descriptive method, with data collection techniques using observation, interviews, and documentation. Involving eleven informants, general informants namely traders and visitors to Lake Shuji tourism and special informants namely village heads, managers and employees of Lake Shuji tourism were determined using purposive sampling technique. Data analysis carried out in this study is SWOT analysis with data reduction, data display, and conclusiondrawing/verification. The criteria for the validity of the data use (credibility) trust, in addition, checking the validity of the data used there are three, extension of observation, increasing persistence, and triangulation. The results of this study indicate that the potential development carried out in Shuji Lake tourism can increase people's income, absorb labor and create new business opportunities for people who switch professions from rubber farmers as traders in Shuji Lake tourism.Shuji Lake Tourism in Lembak Village is equipped with accessibility in the form of good road conditions, the distance from the highway to the destination is easy to reach, and adequate infrastructure facilities. The views of the local community are quite positive and support the existence of Lake Shuji tourism in Lembak Village.